ANALYSIS OF FLEXURAL STRENGTH OF BEAM USING SUBSTITUTION OF BROKEN GLASS BULB AS FINE AGGREGATE ADDITIONAL MATERIAL - FADLUL ADLI; ACHMAD PAHRUL RODJI; SUKADI (CV KULTURA DIGITAL MEDIA, 2024)
Concrete is the main material in building construction, consisting of a mixture of coarse aggregate (gravel), fine aggregate (sand), cement, and water. Concrete is widely used because of its strength, ease of forming, and durability. The SNI standard defines concrete as a mixture of portland cement, aggregate, and water to which other materials can be added to form a solid mass. With the high demand for concrete with compressive and flexural strength, innovations continue to be developed, including the use of substitute materials such as broken glass bulbs to improve concrete quality. This study will examine the effect of broken glass bulbs on the flexural strength of concrete. The use of glass bulb waste increases the flexural strength of concrete. The increase depends on the percentage of waste in the concrete mixture, with test results showing an increase in flexural strength of 0.5 - 2 KN compared to normal concrete. In experiments with 5% and 10% waste, the flexural strength of the beam reached 27 KN and 25 KN after 28 days, respectively, while normal concrete had a flexural strength of 26 KN. These results meet the Indonesian National Standard SNI 03 - 4431 1997.